Answer:
[tex]|-4b - 8| + |1 - b^2| + 2b^2 = 27[/tex]
For [tex]b = 2[/tex]
Step-by-step explanation:
The correct expression is:
[tex]|-4b - 8| + |1 - b^2| + 2b^2[/tex]
Required
Evaluate the expression for [tex]b = 2[/tex]
Substitute 2 for b in [tex]|-4b - 8| + |1 - b^2| + 2b^2[/tex]
[tex]|-4(2) - 8| + |1 - (2)^2| + 2(2)^2[/tex]
Open all brackets
[tex]|-4*2 - 8| + |1 - 2*2| + 2*2*2[/tex]
[tex]|-8 - 8| + |1 - 4| + 8[/tex]
Evaluate all expressions in the absolute value brackets
[tex]|-16| + |-3| + 8[/tex]
In absolute values:
[tex]|-a| = a[/tex]
So, we have:
[tex]16 + 3 + 8[/tex]
[tex]27[/tex]
Hence:
[tex]|-4b - 8| + |1 - b^2| + 2b^2 = 27[/tex]
For [tex]b = 2[/tex]